Development of AMZ composites via mutual attraction of particles in wet processing. Issue 4 (4th May 2020) - Khorsand, Ali; Majidian, Hudsa; Farvizi, Mohammad
ABSTRACT: In this paper, three approaches were investigated for preparing alumina‐mullite‐zirconia (AMZ) composites. The weight ratio of alumina to zircon was selected to be 85/15. In the first approach, common well‐known reaction sintering or solid‐state mixing of alumina and zircon were used. In the second approach, suspensions of the raw materials were prepared to examine the effect of wet processing method. The third approach was based on the use of aluminum alkoxide coated zircon and alumina. The sintering of samples was carried out at the temperature of 1630°C for 3 hours. Phase composition and Rietveld refinement method, microstructural observation, EDS analysis, as well as physical and mechanical properties were used and determined to characterize the sintered samples. The results showed that aluminum alkoxide coating can develop the mentioned reaction sintering and mullite formation. However, the desired mechanical properties were not obtained. Wet processing approach resulted in more interesting data about the formation of mullite and could improve the microstructure homogeneity of final composites. Higher amount of tetragonal zirconia, good densification, high hardness, and fine microstructure were obtained by the wet approach. These interesting results were attributed to the fine discrete particles provided by mutual attraction in the wet preparation method.